Results From a Patient Experience Study in Pediatric Gastrointestinal Endoscopy. (November 2015) - Jacob, Divya Ann; Franklin, Linda; Bernstein, Bruce; Pall, Harpreet
Objective: Gastrointestinal endoscopy in children has become a standard diagnostic and therapeutic modality. The aim of our study was to characterize the most memorable elements of the patient experience from the parent's and patient's perspective and determine ways to improve the overall quality of their experience. Methods: Using a structured questionnaire, we conducted 47 phone interviews with families who had recently undergone gastrointestinal endoscopic procedures. Results: Our study showed clear communication and mutual agreement on care decisions contributed to positive experiences. Inadequate communication of information regarding alternatives to the procedure and risk of complications during the informed consent discussion contributed to negative patient experiences. Standardization of postprocedure follow-up and timely communication of pathology findings also had potential for improvement. Conclusion: Our study revealed 2 areas for quality improvement interventions: The need to ensure that alternatives and complications are thoroughly discussed and the need for standardization of postprocedure follow-up.